Hepatitis C Patients' Self-reported Adherence to Pegylated Interferon and Ribavirin - Weiss, Jeffrey J. (2008)
BACKGROUND: Prior research on adherence to Hepatitis C treatment has documented rates of dose reductions and early treatment discontinuation, but little is known about patients' dose-taking adherence. AIMS: To assess the prevalence of missed doses of pegylated interferon and ribavirin and examine the correlates of dose-taking adherence in clinic settings. METHODS: 180 patients on treatment for Hepatitis C (23% co-infected with HIV) completed a cross-sectional survey at the site of their Hepatitis C care. RESULTS: Seven percent of patients reported missing at least one injection of pegylated interferon in the last four weeks and 21% reported missing at least one dose of ribavirin in the last 7 days. Dose-taking adherence was not associated with HCV viral load. CONCLUSIONS: Self-reported dose nonadherence to Hepatitis C treatment occurs frequently. Further studies of dose nonadherence (assessed by method other than self-report) and its relationship to HCV virologic outcome are warranted.